El laicismo. ¿Una religión metamorfoseada? - Carretero Pasín, Ángel Enrique (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
This article tries, in general lines, to interpret the laity as, in last instance, a transformed religion. Departing, for it, from the sociological perspectives opened by Emile Durkheim and Georg Simmel, it understands the religion as a phenomenon fundamentally societal, linked to certainly of relations established between individuals. First, it introduces us in the peculiar analysis of the sacred thing proposed so much by Durkheim's work as for that of Simmel. Later, it studies the origin and the nature of the laity as a reorientated religion, in the modernity, towards the order of the political thing. Finally, it tries to show the destiny of the laity in the postmodernity, in the context of emergence of a multiple constellation of new deeply rooted religiosidades in the order of the daily thing.